Digital Health Integration With Neuromodulation Therapies: The Future of Patient-Centric Innovation in Neuromodulation - Pathak, Yagna J.; Greenleaf, Walter; Verhagen Metman, Leo; Kubben, Pieter; Sarma, Sridevi; Pepin, Brian; Lautner, Douglas; DeBates, Scott; Benison, Alex M.; Balasingh, Binesh; Ross, Erika (Frontiers in Digital Health, 2021)
Digital health can drive patient-centric innovation in neuromodulation by leveraging current tools to identify response predictors and digital biomarkers. Iterative technological evolution has led us to an ideal point to integrate digital health with neuromodulation. Here, we provide an overview of the digital health building-blocks, the status of advanced neuromodulation technologies, and future applications for neuromodulation with digital health integration.